Voor wie kijken wil. - Eyck, Zsa-Zsa (Wijlre : Kasteel Wijlre, 1986)
Dekkers, Ad ; Struycken, Peter ; Visser, Carel ; Vroegindeweij, Leo ; Long, Richard ; Pope, Nicholas ; Cragg, Tony
Voor wie kijken wil, Kasteel Wylré - Kasteel Wijlre, 14 tot 29 juni 1986
Nederlands
kunstcatalogus